2018
DOI: 10.3389/fnsys.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlate of Transition Violation and Deviance Detection in the Songbird Auditory Forebrain

Abstract: Deviants are stimuli that violate one's prediction about the incoming stimuli. Studying deviance detection helps us understand how nervous system learns temporal patterns between stimuli and forms prediction about the future. Detecting deviant stimuli is also critical for animals' survival in the natural environment filled with complex sounds and patterns. Using natural songbird vocalizations as stimuli, we recorded multi-unit and single-unit activity from the zebra finch auditory forebrain while presenting ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…On the other hand, we suggest that perhaps the increased response in the left NCM reflects a left-dominant sensitivity to aberrant information, resonating with our findings. The left hemisphere of NCM has been shown to be sensitive to novel auditory experience more broadly [ 76 , 77 ] consistent with the idea that NCM (in these studies, bilaterally) is sensitive to expectation [ 78 , 79 ]. Thus perhaps it is the novelty of the distorted song, and not feedback about the bird’s own song per se , that underlies the observed decrease in new neurons in the left NCM.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, we suggest that perhaps the increased response in the left NCM reflects a left-dominant sensitivity to aberrant information, resonating with our findings. The left hemisphere of NCM has been shown to be sensitive to novel auditory experience more broadly [ 76 , 77 ] consistent with the idea that NCM (in these studies, bilaterally) is sensitive to expectation [ 78 , 79 ]. Thus perhaps it is the novelty of the distorted song, and not feedback about the bird’s own song per se , that underlies the observed decrease in new neurons in the left NCM.…”
Section: Discussionsupporting
confidence: 76%
“…For example, after being exposed to sequences of tones with fixed transition patterns, human infants and adults showed surprise responses when they heard sequences that violated the transition patterns in the previously experienced sequences 4,6,7 . Similar statistical learning phenomena have also been reported in songbirds, monkeys and other animals 5,8,9 . However, most laboratory studies at the neural level used the oddball paradigm, in which one stimulus is presented with low probability as oddball while the other stimulus is presented with high probability as standard.…”
Section: Statistical Learning Of Transition Patterns In the Songbird supporting
confidence: 82%
“…However, the enhanced neural responses to the oddball may be because the oddball is rare and therefore unexpected rather than because the oddball violates the repetition pattern of the standard. In addition, in the natural environment, the intervals between sounds are often variable instead of fixed and can span multiple time scales whereas most previous studies have used short and fixed inter-stimulus intervals (ISI) 3,[6][7][8][9]12,14 . Consequently, it is unknown whether there exists a neural correlate of statistical learning of transition patterns when ISI is long or variable.…”
Section: Statistical Learning Of Transition Patterns In the Songbird mentioning
confidence: 99%
“…This suggests that detecting deviance in natural complex sounds is critical for animal survival. Electrophysiological recording studies have reported that the auditory forebrain of songbirds shows larger responses to deviant calls than to standard calls using an oddball paradigm ( Beckers and Gahr, 2012 ; Dong and Vicario, 2018 ). We demonstrated MMR elicited by deviant sounds using an oddball paradigm with song elements and calls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that neurons in NCM show stimulus-specific habituation to natural sounds such as conspecific and heterospecific vocalizations ( Mello et al, 1995 ; Chew et al, 1996 ). In addition, neurons in the secondary auditory areas, i.e., NCM and caudomedial mesopallium (CMM), show response bias to deviant sounds in an oddball paradigm during multiunit and single-unit recordings in both anesthetized birds ( Beckers and Gahr, 2012 ; Ono et al, 2016 ) and awake-restrained birds ( Dong and Vicario, 2018 ). These studies suggest that the NCM integrates auditory information over both long- and short-time windows, and focal attention to auditory stimuli is not required for this process.…”
Section: Introductionmentioning
confidence: 99%